Kryzys azjatycki 1997-1998 jako wstęp do kryzysu finansowego w roku 2007 - Machaj, Mateusz (1997-1998 Asian Crisis as a Prelude to 2007 Financial Crisis, 2008)
Had the 1997-1998 Asian Crisis been properly analyzed, it appears that the crisis from 2007 could have been avoided. The case of South-East Asia ten years ago could have been a great lesson for all the investors. Unfortunately instead of teaching that lesson the authorities intensified negative tendencies in the world economy and stimulated another unsustainable boom which created the illusion of overall prosperity. Unfortunately the current behaviour of public institutions and authorities does not make one an optimist, but rather gloomily suggests that "if history taught us something, it would be that we do not learn from history". Everything indicates that current actions taken by the Fed herald other even more serious problems than those, which we are currently dealing with. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 28, s. 158-166